A clinical study of elective hysterectomies for benign lesions - Meena, Mamta; ., Urvashi; Kachawaha, C. P.; Fatehpuriya, Dharmendra Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Hysterectomy is widely used for treating a variety of gynecologic conditions. Most hysterectomies are elective and are performed to treat benign indications. Hence the present study was undertaken to determine the benign indication of hysterectomy, choice of surgical approach, safety and clinical aspect of hysterectomy as a surgical procedure and to correlate the findings with histopathological reports of the specimen. Methods: The present series represents a clinical study of 120 cases of elective hysterectomies for benign lesions. Out of which 73 were done by abdominal and 47 by vaginal route. Finally, all operated specimen were subjected to histological examination. Results: The main indications for elective hysterectomy were leiomyoma 53 (44.2%), prolapse 47 (39.2%) and dysfunctional uterine bleeding 11 (9.2%). Type of operation performed were mainly total abdominal hysterectomy with bilateral salphingo-oophorectomy in 60% cases and vaginal hysterectomy with anterior and posterior repair in 38.3% cases. The mean duration of surgery and average blood loss was more in vaginal procedure (90 min and 100ml) compared to abdominal (70 min and 80ml) respectively. Vaginal hysterectomy was associated with less morbidity and a smoother convalescence than abdominal hysterectomy. In 81.2% cases of abdominal hysterectomies correspondence of indication with histopathological report (HPR) were found, in vaginal 74.5% cases corresponded their histopathological report with their symptoms and investigations. Associated adnexal pathology was found in 8.3% cases. There was no mortality during the whole study period. Conclusions: Hysterectomy for benign pelvic lesions is a safe procedure and an important component of health care for women.